Evaluation of the bone regenerative effect of glycogen synthase kinase 3 antagonist Tideglusib carried by different scaffolds on rat calvarial defects - Calik, Muemin; Unal, Semra; Alemdag, Berna; Gunduz, Oguzhan; Tekkesin, Merva Soluk; Ozen, Bensu; Islek, Ipek; Kuru, Leyla; Agrali, Omer Birkan (ELSEVIER, 2025)
The aim was to explore the efficiency of Tideglusib in bone tissue healing by carrying it with different scaffolds on rat calvarial lesions. Twentyfour male Dawley rats were utilized. Two bone defects of 5 mm in diameter were formed (n = 8). Groups constituted negative control, collagen sponge + Tideglusib (CT), bacterial cellulose carrier (BC), bacterial cellulose carrier + Tideglusib (BC + T), PCL/Gel nanocarrier (Nano) and PCL/Gel + Tideglusib (Nano+T). After four week, histomorphometric and immunohistochemistry investigations were performed. Pairwise comparisons by means of the new bone formation (NBF) effect of Tideglusib demonstrated a significant difference between the control and the Nano+T groups solely (p < 0.05). BC group demonstrated reduced NBF in comparison to the CT group (p < 0.05), Nano group (p < 0.01) and Nano+T group (p < 0.01). Similarly, the BC + T group exhibited a diminished rate of NBF in comparison to both the Nano (p < 0.01) and Nano+T groups (p < 0.01). Type I collagen expression decreased in the BC group (p < 0.05) and BC + T group (p <0.05) relative to the control. Axin2 expression was increased in the Nano+T group (p < 0.05) compared to the control. Within the limits, Tideglusib delivered with a nanocarrier containing PCL/Gel may have favorable impact on bone regeneration. However, the impact may vary with different carrier.
Keywords: GSK-3 inhibitor; Tideglusib; Wnt signaling pathway; BACTERIAL CELLULOSE; MEMBRANE; DELIVERY; COLLAGEN; CATENIN; ACID; Biochemistry & Molecular Biology; Chemistry; Polymer Science